Long-term clinical outcomes and prognostic factors of upfront surgery as a first-line therapy in biopsy-proven clinical N2 non-small cell lung cancer - Bertolaccini, Luca; Prisciandaro, Elena; Guarize, Juliana; Girelli, Lara; Sedda, Giulia; Filippi, Niccolò; de Marinis, Filippo; Spaggiari, Lorenzo (Frontiers in Oncology, 2022)
Background. Multimodality therapy offers the best opportunity to improve pathological N2 non-small cell lung cancer (NSCLC) prognosis. This paper aimed to evaluate the long-term clinical outcomes and the prognostic factors of upfront surgery as first-line therapy in biopsy-proven clinical N2. Methods. Retrospective review of biopsy-proven cN2 NSCLC patients operated between 2007 and 2017. Upfront surgery was considered if the primary tumour was deemed completely resectable, with mediastinal nodal involvement confined to a single station and no preoperative evidence of extranodal tumour invasion. Results. 285 patients who underwent radical resections were included. 159 patients (55.8%) received induction chemotherapy. At follow-up completion, 127 (44.6%) patients had died. For the induction chemotherapy group, the median OS was 49 months [95% confidence interval (CI): 38–70 months], and 5-year OS was 44.4%. The median and 5-year OS for the upfront surgery group were 66 months (95% CI: 40–119 months) and 66.3%, respectively. There were no statistically significant differences between treatment approaches (p=0.48). One hundred thirty-four patients (47.0%) developed recurrence. The RFS at 5-years was 17% (95% CI: 11–25%) for induction chemotherapy and 22% (95% CI: 9–32%) for upfront surgery; there were no statistically significant differences between groups (p=0.93). No significant differences were observed based on the clinical N status (OS, p=0.36; RFS, p=0.65). Conclusions. Upfront surgery as first-line therapy for biopsy-proven cN2 NSCLC showed favourable clinical outcomes, similar to those obtained after induction chemotherapy followed by surgery. Therefore, it should be considered one of the multimodality treatment options in resectable N2 NSCLC.